Art in its time : theories and practices of modern aesthetics - Mattick, Paul, 1944- (Routledge, 2003)
Art In Its Time takes a close look at the way in which art has become integral to the everyday 'ordinary' life of modern society. It explores the prevalent notion of art as transcending its historical moment, and argues that art cannot be separated from the everyday as it often provides material to represent social struggles and class, to explore sexuality, and to think about modern industry and our economic relationships. The way we view art is a phenomenon of modern society and its social order. It is only in the 18th century that we see the exaltation of art through the rise of museums, today sites of mass pilgrimage and focal to modern activity. On the one hand, this confirms the art historian's notion that art is an autonomous narrative and that its value is independent of practical interest; yet, on the other hand, we know that art comes out fo the everyday life and it can attain higher value by its success in entering the stream of 'art', and by its exchange-value, the expression in money of the art-lover's desire.; Paul Mattick explores many of the ideas that surrround art today including Modernism, the sublime and beautiful, the relationship between art and money and particularly philanthropy in the US, the role of photography in producing the aesthetic 'ara' and the limits of political art. Art In Its Time is a valuable contribution to the ongoing debate on the role of art particularly as modern art continues to depart from traditional notions of what art is. Providing a much needed social history of art, Art and Its Time will be of interest to all students of art theory and art history.